Appendicitis during the COVID-19 lockdown: results of a multicenter analysis in Germany - Willms, Arnulf; Oldhafer, Karl J.; Conze, Sophie; Thasler, Wolfgang E.; von Schassen, Christian; Hauer, Thorsten; Huber, Tobias; Germer, Christoph-Thomas; Günster, Simone; Bulian, Dirk R.; Hirche, Zarah; Filser, Jörg; et al. (Langenbeck's archives of surgery, 2021)
The COVID-19 pandemic has transformed medical care worldwide. General surgery has been affected in elective procedures, yet the implications for emergency surgery are unclear. The current study analyzes the effect of the COVID-19 lockdown in spring 2020 on appendicitis treatment in Germany.
Gesehen am 13.07.2021